Answer:
-2
Step-by-step explanation:
m=(y2-y1)/(x2-x1)
m=(10-2)/(-9-(-5))
m=8/(-9+5)
m=8/-4
m=-2
Please mark me as Brainliest if you're satisfied with the answer.
Answer:
Washington
Step-by-step explanation:
<span>A number, half of that number, and one-third of that number are added.
This statement can be expressed as:
x + (1/2)x + (1/3)x
The total is 22
</span>x + (1/2)x + (1/3)x = 22
So let's look for x
x + (1/2)x + <span>(1/3)x = 22
</span>(6x + 3x + 2x) / 6 = 22
11x = 132
x = 12
So the original number is 12.
5.7 - 0.38 = 5.70 - 0.38 = 5.32
70 - 38 = 32
Answer:
x = √2 + 2, -√2 + 2
Step-by-step explanation:
y = -2(x-2)² + 4
-2(x-2)² + 4 = 0 --- replace y with 0
-2(x - 2)² = -4 --- subtract 4 from both sides
(x - 2)² =
--- divide both sides by -2
(x - 2)² = 2 --- simplify
x - 2 = +-√2 --- square root both sides
x - 2 = √2 --- split into 2 equations
x - 2 = -√2
x = √2 + 2 --- solve first equation
x = -√2 + 2 --- solve second equation
x = √2 + 2, -√2 + 2